MPR Annual Session and Substantial Democracy: Considering the Relevance of Constitutionalism and Popular Sovereignty in the Governance of Indonesian Democracy - Mohammad Reza; Azis Budianto (Jurnal Multidisiplin Indonesia, 2025)
The institutional transformation of the People's Consultative Assembly (MPR) post-reformation has shifted its constitutional role from the highest state institution to one of the important pillars in the state system that emphasizes the principle of division of powers. The MPR Annual Session emerged as a forum that accommodates the submission of annual reports of state institutions and the President's state address. However, the effectiveness of this forum is still questionable: is it merely ceremonial or does it play a role in strengthening substantial democracy based on people's sovereignty and constitutionalism? This paper examines the relevance of the MPR Annual Session in strengthening substantial democracy in Indonesia through a normative-constitutional approach and the theory of people's sovereignty. The focus of the analysis is directed at the potential of this forum as an accountable deliberative instrument, to strengthen transparency and the mechanism of checks and balances between state institutions. This article argues that strengthening the role of the MPR Annual Session is not merely symbolic, but important in facing the challenges of procedural democracy and oligarchic tendencies in policy practice. Thus, the institutional reform of the MPR Annual Session is a strategic step to realize a more inclusive, responsive, and equitable constitutional democracy.